A clash of values: Deep-rooted discord between empowering, participatory, community-driven development and results-focused, evidence-based evaluation. Issue 5 (20th October 2021) - M. Kelly, Leanne
ABSTRACT: Evaluation is experiencing increasing popularity with Western-leddiscourse hailing the worth of evidence-based practice, results based management, measurement, and value for money. While this orthodoxy of evaluation has been subjected to substantial critique, dissenting voices and local ways of doing have been over powered by the dominant paradigm, which privileges certain types of evidence over others. This paper examines the evident disconnects that occur when the evaluation orthodoxy is applied to evaluation of community development interventions. As such, the paper examines extreme ends of the continuum to illustrate deep-rooted epistemological divergences between the positivist, reductionist, top-down evaluation orthodoxy that is profoundly at odds with the constructivist, complex, experience-valuing, bottom up values of community development. This paper suggests that evaluation practice must deeply consider values and principles central to community development theory so evaluation can support and enhance, rather than hinder and contradict, the processes and outcomes that community development interventions strive to realize.